The effect of land transportation infrastructure on congestion in Jayapura City - Ramandei, Lazarus (Jurnal Penelitian Saintek, 2025)
The transportation sector has a significant impact on the environment, particularly in terms of urban air pollution, congestion, and road damage. Nevertheless, transportation remains essential to support economic activity, education, and daily work. This study aims to determine the effect of land transportation infrastructure on congestion in Jayapura City. This research employed a qualitative approach, with data collected through questionnaires. The data were analyzed using simple regression analysis.  The results showed that land transportation infrastructure has a significant effect on congestion in Jayapura City. Based on the partial t-test using SPSS, a t value of -8.957 was obtained with a probability value (sig value) of 0.000. Since this probability value is smaller than alpha (5%), it can be concluded that land transportation infrastructure partially has a significant effect on congestion. This study confirms that the improvement and management of land transportation infrastructure is essential to reduce congestion in Jayapura City, which in turn can support economic activities, education, and daily work.